The Interplay between Obstructive Sleep Apnea and Atrial Fibrillation - Marulanda-Londoño, Erika; Chaturvedi, Seemant (Frontiers in Neurology, 2017)
Atrial fibrillation is the most common cardiac arrhythmia. Obstructive sleep apnea is also an increasingly common condition. Both entities are risk factors for ischemic stroke and both conditions are linked with increased mortality. Mechanical effects of obesity and sleep apnea can lead to increased afterload, left ventricular hypertrophy, and left atrial fibrosis and remodeling. These changes can result in an increased risk of atrial fibrillation development. The current paper summarizes the evidence for the bidirectional relationship between atrial fibrillation and obstructive sleep apnea. The merits of selective screening for these two conditions is also discussed.